2021
DOI: 10.3389/fonc.2021.694634
|View full text |Cite
|
Sign up to set email alerts
|

Application of Diffusion Weighted Imaging Techniques for Differentiating Benign and Malignant Breast Lesions

Abstract: To explore the value of apparent diffusion coefficient (ADC), intravoxel incoherent motion (IVIM), and diffusional kurtosis imaging (DKI) based on diffusion weighted magnetic resonance imaging (DW-MRI) in differentiating benign and malignant breast lesions. A total of 215 patients with breast lesions were prospectively collected for breast MR examination. Single exponential, IVIM, and DKI models were calculated using a series of b values. Parameters including ADC, perfusion fraction (f), tissue diffusion coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
7
2
Order By: Relevance
“…The region of interest (ROI) was delineated on the grayscale map with a b-value of 1,000 s/mm 2 (12), and then, the pseudocolor images of the IVIM and DKI parameters were merged with the grayscale map by using 3D SynchroView (GE Healthcare) (Figure 2). The ROI included as much of the solid region of the tumor as possible, while regions with large blood vessels, necrosis, or hemorrhage were avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The region of interest (ROI) was delineated on the grayscale map with a b-value of 1,000 s/mm 2 (12), and then, the pseudocolor images of the IVIM and DKI parameters were merged with the grayscale map by using 3D SynchroView (GE Healthcare) (Figure 2). The ROI included as much of the solid region of the tumor as possible, while regions with large blood vessels, necrosis, or hemorrhage were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has a greater sensitivity than mammography or ultrasound in the diagnosis of breast cancer (12). Both dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) can detect the microscopic features of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been many reports on the differential diagnosis of benign and malignant breast lesions using MK and MD values, which have reported improved sensitivity and accuracy in differentiating between benign and malignant breast lesions [ 1 , 2 , 14 ]. Nogueira et al [ 21 ] reported that MK was one of the representative parameters of DKI technology and a useful index to measure the complexity of organizational structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increasing interest in diffusion kurtosis imaging (DKI) to assess non-Gaussian diffusion behavior in diseases involving complex biological tissues such as breast cancer [ 11 13 ]. DKI technology has been shown to improve the sensitivity and accuracy for diagnosing benign and malignant breast lesions and is therefore regarded as a promising technique for the differential diagnosis of breast lesions [ 14 , 15 ]. DKI can measure molecular water movement via ADC values.…”
Section: Introductionmentioning
confidence: 99%
“…IVIM assessment in the imaging of several organs has drawn increased attention in recent years, for instance, in the imaging of normal livers and livers with cirrhosis (11)(12)(13)(14) , kidney, (15)(16)(17) , and the prostate (10,18) There was, however, no established technique or ideal set of b-values to distinguish between the diffusion or perfusion effects. Instead, multiple ranges of b-values were employed in the clinical assessment of IVIM characteristics from various institutions (2,19,20) .…”
Section: Introductionmentioning
confidence: 99%